B Cell signaling and Immunosuppression in Geriatrics: A Review - Adepoju, A. Emmanuel-Funsho1,2*, Igbe, M. Ikwoegbu1,3, Babajimi-Joseph Amarachi1,4, Elujoba Samson1,5, Adamu, A. Ibrahim1,6, Muhibi, A. Musa1 (Sokoto Journal of Medical Laboratory Science)
The human immune system undergoes significant changes with age, leading to a phenomenon termed immunosenescence- A decline in immune functionality. This decline in immune function is characterized by a diminished ability to respond to novel antigens and increased susceptibility to infections. B cells, responsible for antibody production and humoral immunity, are particularly affected by immunosenescence. This review explores the intricate interplay between B cell signaling p a t h w a y s a n d t h e d e v e l o p m e n t o f immunosuppression in the elderly. It also discusses the alterations in B cell receptor (BCR) signaling, co-stimulatory molecules, and the influence of the inflammatory environment on B cell function. Additionally, the impact of chronic co-morbidities prevalent in geriatrics on B cell signaling was examined. Finally, the potential therapeutic strategies to rejuvenate B cell responses secondary to an enhanced vaccine efficacy in older adults was examined.